2012 IEEE Power and Energy Society General Meeting 2012
DOI: 10.1109/pesgm.2012.6345563
|View full text |Cite
|
Sign up to set email alerts
|

Parameter estimation of dynamic load model using field measurement data performed by OLTC operation

Abstract: An accurate representation of the dynamic behavior of an electrical load is very important for the analysis of power system operation regarding its stability characteristics, especially for voltage stability analysis. This paper presents the practical experience of dynamic load modeling using the real system measurement data. In order to capture the dynamic behavior of the power system on a load bus, a perturbation was introduced into the system by adjusting the transformer OLTC (on-load tap changer). That cau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 12 publications
0
3
0
3
Order By: Relevance
“…En la literatura se han utilizado una gran cantidad de técnicas y metodologías de optimización. Algunas de las más utilizadas son: mínimos cuadrados, mínimos cuadrados no lineales y similares [23]- [31]; Levenberg-Marquardt [32], [33]; algoritmos genéticos [34]- [38]; optimización por enjambre de partículas [39], [40]; redes neuronales artificiales [41]- [43]; filtro de Kalman [44]; ajuste vectorial [45]; máquinas de soporte vectorial [46] y; árbol de decisiones [47].…”
Section: Tipo De Identificación Paramétrica (C4)unclassified
See 2 more Smart Citations
“…En la literatura se han utilizado una gran cantidad de técnicas y metodologías de optimización. Algunas de las más utilizadas son: mínimos cuadrados, mínimos cuadrados no lineales y similares [23]- [31]; Levenberg-Marquardt [32], [33]; algoritmos genéticos [34]- [38]; optimización por enjambre de partículas [39], [40]; redes neuronales artificiales [41]- [43]; filtro de Kalman [44]; ajuste vectorial [45]; máquinas de soporte vectorial [46] y; árbol de decisiones [47].…”
Section: Tipo De Identificación Paramétrica (C4)unclassified
“…La estimación del modelo dinámico ERL con registros de eventos ha sido estudiado en [26], [31], [33], [44], [58]. Las técnicas utilizadas son: mínimos cuadrados, mínimos cuadrados no lineales [26], [31], [58], "Levenberg -Marquardt" [33] y, "Unscented Kalman Filter" [44].…”
Section: Tipos De Mediciones (C6)unclassified
See 1 more Smart Citation
“…In [52] the authors demonstrated the procedure of dynamic load modeling by using real-world measurements. To capture, i.e., record load dynamics, voltage perturbations were introduced by altering tap settings on the transformer ULTC, thus changing the voltage on the secondary (load) side.…”
Section: Electric Load Compositionmentioning
confidence: 99%
“…The weighted least squares method has been applied in [5] to derive the load model. In [6], the nonlinear least square (NLS) technique is used to identify the parameters of a dynamic recovery load in the presence of voltage changes due to load tap changer operation. An improved NLS method is proposed in [7], however, an initial guess on parameter values is required for the estimation.…”
Section: Introductionmentioning
confidence: 99%